2022
DOI: 10.3390/jrfm15110514
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Financial Stability: The Case of Commercial Banks in Vietnam

Abstract: Bank stability is a goal that bank managers aim for in addition to the goal of maximizing shareholder value. To achieve this goal, commercial banks have applied various solutions, including corporate governance because corporate governance plays an important role in the business activities of an enterprise in general as well as in that of a commercial bank in particular. The purpose of this paper is to investigate the impact of corporate governance on the stabilities of Vietnamese commercial banks in the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
2
2
0
Order By: Relevance
“…In hypothesis testing it can be concluded that the hypothesis is accepted where there is a significant positive influence of inflation on ROA. The results of this test are in line with research results from Batsinda & Shukla (2019) and Nguyen (2019) which state that inflation is a macroeconomic variable that has a positive impact on bank performance. With inflation, prices of goods and services will increase, and bank interest rates will also increase.…”
Section: Inflation Has a Significant Effect On Roasupporting
confidence: 86%
See 1 more Smart Citation
“…In hypothesis testing it can be concluded that the hypothesis is accepted where there is a significant positive influence of inflation on ROA. The results of this test are in line with research results from Batsinda & Shukla (2019) and Nguyen (2019) which state that inflation is a macroeconomic variable that has a positive impact on bank performance. With inflation, prices of goods and services will increase, and bank interest rates will also increase.…”
Section: Inflation Has a Significant Effect On Roasupporting
confidence: 86%
“…In hypothesis testing it can be concluded that the hypothesis is accepted where there is a significant positive influence of Economic Growth on ROA. The test results are in line with the findings from (Boussaada et al, 2023;Gupta & Mahakud, 2020;Nguyen, 2019). High GDP growth can create a good economic climate, increase market demand, and encourage consumption and corporate investment.…”
Section: Economic Growth Has a Significant Effect On Roasupporting
confidence: 82%
“…Few empirical studies on commercial banks have found leverage and profitability to have a muddled relationship (Abbas et al, 2019). Profitability is negatively correlated with the total debt ratio and the short-term debt ratio, but positively correlated with the long-term debt ratio (Nguyen, 2023), It was determined that there exists an inverse relationship between profitability and capital ratio in the financial industry (Hasbiah, 2022). Gropp and Heider (2010) observed that book leverage and market leverage have a negative correlation with profitability(Lapavitsas & Mendieta-Muñoz, 2019).…”
Section: Literature Review 21 Financial Gainsmentioning
confidence: 99%
“…The intensity of competition has reached an unprecedented level, requiring companies to rely on innovation, operational optimization, and efficiency improvement to maintain their competitive position (Gomez & Guzman, 2021). Price fluctuations and transitions in economic cycles pose significant risks to corporate financial investment, requiring strong risk management capabilities (Nguyen & Nguyen, 2020). Moreover, the uncertainty of the market economy requires companies to flexibly adjust their financial investment strategies in the context of ever-changing market conditions.…”
Section: Introductionmentioning
confidence: 99%